The Ethical Dilemma and Integrity of the Notary Role in the Execution of Cyber Notary: Challenges to the Requirement of Physical Deed Review - Andy Tallu Padang; Ayu Putrijanti (CV WAHANA PUBLIKASI, 2026)
The rapid progression of information technology and the expansion of the digital economy have increased the demand for notarial services that are efficient, accessible, and electronically integrated. In Indonesia, the concept of cyber notary is recognised to a limited degree in the Elucidation of Article 15 paragraph (3) of the Law on Notarial Office (UUJN). The UUJN stipulates that deeds must be read in the presence of the concerned parties and signed simultaneously, underscoring the requirement for personal attendance. This disparity creates an ethical challenge and may undermine the integrity of the notarial profession, since efforts to modernise notarial services can conflict with the legal requirements that verify the authenticity of notarial deeds. This article examines compliance with the standards of vigilance and prudence required of notaries in providing electronic services, particularly with identity verification, legal capacity, informed consent, and the reading of deeds. It also analyses the normative boundaries of the expression “before the appearing parties” in a digital setting. The research employs a normative legal framework, supported by empirical data obtained from literature reviews and extensive interviews with notaries. The results provide an ethical and operational basis for cyber notary activities rooted in notarial due process. The framework emphasises comprehensive identity verification, verifiable documentation of the notarial process, protections against coercion, system security and data protection measures, as well as limitations on technology use during the pre-deed phase and in the certification of electronic transactions. From a policy perspective, normative harmonisation is crucial to ensure that digital change bolsters legal certainty while maintaining the legitimacy of notarial acts and the integrity of the notarial profession.